2019
DOI: 10.1371/journal.pone.0213037
|View full text |Cite
|
Sign up to set email alerts
|

Migratory goose arrival time plays a larger role in influencing forage quality than advancing springs in an Arctic coastal wetland

Abstract: With warmer springs, herbivores migrating to Arctic breeding grounds may experience phenological mismatches between their energy demands and the availability of high quality forage. Yet, how the timing of the start of the season and herbivore arrival influences forage quality is often unknown. In coastal western Alaska, approximately one million migratory geese arrive each spring to breed, where foliar %N and C:N ratios are linked to gosling survival and population growth. We conducted a three-year experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 90 publications
4
14
0
Order By: Relevance
“…Warmer weather during the growing season may decrease leaf‐level nitrogen (N) and increase concentrations of anti‐herbivory compounds in spring and summer forage (Jonasson et al 1986, Turunen et al 2009, Zamin et al 2017). Warmer temperatures may also result in phenological mismatch (Post and Forchhammer 2008, Beard et al 2019). Though caribou exhibit significant physiological and behavioral resilience to phenological mismatches (Mallory et al 2020), shift of the growing season earlier into the spring could decouple annual caribou physiological stages like parturition and lactation from both the timing and seasonality of critical nutrients on the landscape (Walsh et al 1997, Fauchald et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Warmer weather during the growing season may decrease leaf‐level nitrogen (N) and increase concentrations of anti‐herbivory compounds in spring and summer forage (Jonasson et al 1986, Turunen et al 2009, Zamin et al 2017). Warmer temperatures may also result in phenological mismatch (Post and Forchhammer 2008, Beard et al 2019). Though caribou exhibit significant physiological and behavioral resilience to phenological mismatches (Mallory et al 2020), shift of the growing season earlier into the spring could decouple annual caribou physiological stages like parturition and lactation from both the timing and seasonality of critical nutrients on the landscape (Walsh et al 1997, Fauchald et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Person et al (1998) and Beard et al (2019) argued that grazing response delayed senescence and maintained peak nitrogen content longer into the season than for ungrazed plots. It may be that a similar response does not occur after the peak and during the seasonal decline in nitrogen content (Beard et al 2019). Alternatively, we may not have had sufficient grazing pressure to stimulate a detectable response in the plants.…”
Section: Discussionmentioning
confidence: 99%
“…At the Colville River Delta, Alaska, USA (150 km east of our study area), Sedinger et al (2001) and Hupp et al (2017) found very little grazing offtake, similar to what we measured at the Smith River. Person et al (1998) and Beard et al (2019) argued that grazing response delayed senescence and maintained peak nitrogen content longer into the season than for ungrazed plots. It may be that a similar response does not occur after the peak and during the seasonal decline in nitrogen content (Beard et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…plant resources; Figure ; Nakazawa & Doi, ). Thus far, empirical studies in terrestrial systems investigating phenological mismatch at the lower trophic level have focused on the reductions in forage quality for herbivores (Beard et al, ; Doiron, Gauthier, & Lévesque, ; Lameris et al, ; Zamin, Côté, Tremblay, & Grogan, ), and how mismatches between plants and pollinators influence seed production (Forrest, ; Kudo & Ida, ). An often‐overlooked component is how phenological mismatches influence the producer itself (i.e.…”
Section: Introductionmentioning
confidence: 99%